2022
DOI: 10.3389/fendo.2022.861760
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Glucose Index Is More Closely Related to Hyperuricemia Than Obesity Indices in the Medical Checkup Population in Xinjiang, China

Abstract: BackgroundHyperuricemia (HUA) is a metabolic anomaly with an increased incidence rate, causing a global medical burden. Several studies have confirmed that obesity and insulin resistance (IR) are the risk factors for HUA. Reports on the predictive power of different obesity indices for HUA are limited. This study aimed to compare the association between different general, abdominal, and visceral obesity indices and markers of the IR-triglyceride glucose (TyG) index with serum uric acid (SUA) and to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…Shi et al 21 performed cross-sectional studies on 6,466 subjects and revealed that TyG was positively related to hyperuricemia after adjusting for potential confounding factors. Kahaer et al 22 performed a cross-sectional analysis on 2,243 patients in a medical check-up population from Xinjiang, China, and the results revealed that the TyG index was more closely associate with hyperuricemia than obesity indices. Yu et al 23 performed a cross-sectional study on adults with hypertension, and showed that a higher level of TyG was associated with a higher risk of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al 21 performed cross-sectional studies on 6,466 subjects and revealed that TyG was positively related to hyperuricemia after adjusting for potential confounding factors. Kahaer et al 22 performed a cross-sectional analysis on 2,243 patients in a medical check-up population from Xinjiang, China, and the results revealed that the TyG index was more closely associate with hyperuricemia than obesity indices. Yu et al 23 performed a cross-sectional study on adults with hypertension, and showed that a higher level of TyG was associated with a higher risk of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that insulin resistance is a pathophysiological process that is closely associated with hyperuricemia 17 ,and hyperinsulinemia caused by insulin resistance can cause renal urate excretion reduce, resulting in blood urate accumulation 18 . Recent studies have revealed the correlation between TyG index and hyperuricemia, and the correlation was stronger than that between obesity indices and hyperuricemia among general Chinese populations 19 22 . In addition, in a cross-sectional study, the TyG index and hyperuricemia were also positively correlated in hypertensive adults 23 .…”
Section: Introductionmentioning
confidence: 94%
“…2.2 According to the definition from “Guidelines for Diagnosis and Treatment of Hyperuricemia and Gout in China (2019)”, two measurements on different days, UA > 420 μmol/l is considered hyperuricemia ( 13 ). Therefore, based on the previous studies ( 12 , 14 ), it was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…Although obesity indicators and insulin resistance index can predict the risk of HUA ( 11 , 12 ), the more suitable indicator for predicting the risk of HUA in Chinese college students has yet to be concluded. Therefore, this study used a cross-sectional survey to analyze and compare the three indices of visceral adiposity (LAP index, ABSI, and BRI), general adiposity index (BMI), abdominal adiposity index (WC and WHtR), with the TyG index and its derivatives to predict the risk of HUA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the pathophysiological process of insulin resistance is closely associated with hyperuricemia 17 and hyperinsulinemia caused by insulin resistance, can cause renal urate excretion to be reduced, resulting in blood urate accumulation 18 . Recent studies have revealed the correlation between TyG index and hyperuricemia, and the correlation was more closely than that between obesity indices and hyperuricemia among general Chinese populations [19][20][21][22] . In addition, in a cross-sectional study, the TyG index and hyperuricemia were also positively correlated in hypertensive adults 23 .…”
Section: Introductionmentioning
confidence: 92%